2021
DOI: 10.7717/peerj.10844
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and functional profiling of the rhizosphere microbiomes of the invasive weed Ageratina adenophora and native plants

Abstract: The rhizosphere soil microbiome (RSM) plays an important role in the nutritional metabolism of the exotic weed Ageratina adenophora. However, our understanding of the composition and metabolic activity of this microbiome is limited. We used high-throughput sequencing of bacterial 16S rRNA genes and fungal internal transcribed spacer fragments in combination with transcriptome analysis to compare the composition and metabolic features of the RSMs of A. adenophora and the native plant species Artemisia indica an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Du et al 10.3389/fmicb.2023.1131797 Frontiers in Microbiology 10 frontiersin.org by significantly enhancing the N and P of the former. Therefore, AMFcan enhance A. adenophora's competitiveness by providing more nutrients, which may be attributed to their different AMF colonization rates (Waller et al, 2016;Xia et al, 2021). Compared to monoculture treatment, the AMF colonization rate of R. amethystoides was significantly decreased, while the AMF colonization rate of A. adenophora was significantly increased when the two plant species were in interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…Du et al 10.3389/fmicb.2023.1131797 Frontiers in Microbiology 10 frontiersin.org by significantly enhancing the N and P of the former. Therefore, AMFcan enhance A. adenophora's competitiveness by providing more nutrients, which may be attributed to their different AMF colonization rates (Waller et al, 2016;Xia et al, 2021). Compared to monoculture treatment, the AMF colonization rate of R. amethystoides was significantly decreased, while the AMF colonization rate of A. adenophora was significantly increased when the two plant species were in interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…aquimarina , were found in rhizospheric soil of A. adenophora ( Figure 1 ). The invasion of A. adenophora selected specific microbial taxa in soil, which may have mediated soil nutrient cycling and thus potentially improved plant nutrient acquisition ( Xia et al, 2021 ; Li et al, 2022 ). Different Bacillus taxa vary in their ability to supply plants with nutrients ( Pinyapach et al, 2018 ; Kang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, A. adenophora invasion leads to a decrease in actinomycetes but increases in aerobic, anaerobic bacteria, and nitrogen-fixing bacteria ( Niu et al, 2007 ; Xu et al, 2012 ; Fang et al, 2019 ). The rhizospheric soil microbiomes of A. adenophora differed to varying degrees in the relative abundances of bacterial and fungal phyla and genera from those of two native plants, Artemisia indica and Imperata cylindrica , and were more metabolically active than both of these, as indicated by marked increases in the expression levels of genes associated with the cell wall, cell membrane, and envelope biogenesis, energy production and conversion, and the transport of carbohydrates, amino acids, coenzymes, nucleotides, and secondary metabolites ( Xia et al, 2021 ). Previous studies have reported that A. adenophora can result in the accumulation of Bacillus , such as B. megaterium and B. cereus , which might significantly promote the growth of A. adenophora compared to native plants ( Niu et al, 2007 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in some species, such as Crotalaria, nodulation is required for alkaloid production [7]. Functional analysis of soil metagenomic data has expanded as a field, and is used as a way to consider how plants are influencing the microbiome [8]. The microbiome is equally important in understanding plant secondary metabolism.…”
Section: The Significance Of the Plant Microbiomementioning
confidence: 99%